Rape and serious sexual assault against women aged 60 and over - BOWS, HANNAH (2017)
Despite the vast amount of research attention examining sexual violence against women, and an increase in research around abuse of older people over the last two decades, sexual violence against people aged 60 and over remains under-researched. As the world population continues to rapidly age, there is a pressing need to address this gap in research in order to inform policy and practice in preventing and responding to sexual violence. This thesis contributes to three existing, but currently distinct, fields of inquiry: elder abuse; domestic violence against older women; and sexual violence against older women. A multi-methodological multi-stage approach was adopted to examine the extent and nature of sexual violence against older women in the UK and the characteristics of victims, perpetrators and incidents through analysis of police data gained through Freedom of Information requests. Interviews with 23 practitioners working in sexual violence organsiations and 4 working in age-related organisations shed light on some of the challenges older survivors may experience when accessing support services, the key support needs of older survivors and the extent to which practitioners felt comfortable in meeting those needs. Gaps in current service provision were also explored. In the final stage, three women survivors of sexual violence since the aged of 60 shared their stories, in particular the physical and emotional impacts sexual violence had on the and providing accounts of their experiences of accessing support services. Their thoughts on issues with current support provision and existing gaps were also shared. This thesis considers these findings collectively to examine for the first time the extent, nature and impacts of sexual violence against women aged 60 and over